2008
DOI: 10.1208/s12249-008-9117-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Drug Release of Chitosan Sponge Containing Doxycycline Hyclate

Abstract: Abstract. The purpose of the present study was to develop and characterize the chitosan sponges loading with doxycycline hyclate and their antibacterial activities. The pore density of chitosan sponge prepared with freeze drying technique was increased as the higher concentrated chitosan solution was used. The sponge prepared from 10% w/w of the chitosan solution and crosslinking with glutaraldehyde solution was utilized for loading with doxycycline hyclate. The drug release and sustainable antibacterial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 14 publications
2
26
0
5
Order By: Relevance
“…This is why an extension of Peppas model to the Power law model (0<n<1) is generally applied in order to elucidate the complex kinetic mechanisms involved in the drug release from such natural supports. Practically, n value includes characteristics of each particular model previously described (Ghica et al, 2009;Albu et al, 2009a;Albu et al, 2010b;Phaechamud & Charoenteeraboon, 2008;Natu et al, 2007). Our studies showed values of n equal to 0.5 for different collagen-based hydrogels with doxyciclyne, uncross-linked or cross-linked with glutaraldehyde, which confirms the respect of Higuchi model concerning the drug release from semisolid supports (Albu et al, 2009b).…”
Section: Fig 4 Drug Release From Collagen Matrixsupporting
confidence: 85%
“…This is why an extension of Peppas model to the Power law model (0<n<1) is generally applied in order to elucidate the complex kinetic mechanisms involved in the drug release from such natural supports. Practically, n value includes characteristics of each particular model previously described (Ghica et al, 2009;Albu et al, 2009a;Albu et al, 2010b;Phaechamud & Charoenteeraboon, 2008;Natu et al, 2007). Our studies showed values of n equal to 0.5 for different collagen-based hydrogels with doxyciclyne, uncross-linked or cross-linked with glutaraldehyde, which confirms the respect of Higuchi model concerning the drug release from semisolid supports (Albu et al, 2009b).…”
Section: Fig 4 Drug Release From Collagen Matrixsupporting
confidence: 85%
“…The combined vancomycin/tobramycin elution data were found to generally be well defined by the four investigated kinetic models (Table ). The release component of the models, n , was often found to be 0.45 which suggests that the antibiotic elution profile is complex in nature and that a power law alone cannot be fully characterize the behavior . The coupled mechanism model resulted in the best fit to the experimental data (based on the R 2 values), however, the zero value obtained frequently for the burst effect component makes physical interpretation difficult (these values could be an aberration from the curve fitting procedure).…”
Section: Resultsmentioning
confidence: 99%
“…The zones of inhibition obtained by Phaechamud and Charoenteeraboon using chitosan sponge loaded with 50 mg doxycycline against E. coli and S. aureus were approximately 35 mm. It should be noted that our collagen and ELP‐collagen hydrogels with 5% w/w doxycycline contained only ∌33 ”g of doxycycline and yet produced 8−12 mm and 25−30 mm zones of inhibition against E. coli and MRSA , respectively . While doxycycline has been shown to be effective against S. sanguinis , no studies have been reported using release of doxycycline from hydrogels to inhibit S. sanguinis growth.…”
Section: Discussionmentioning
confidence: 97%